Determinants of COVID-19 Related Perception among University of Gondar Academic Staff, Gondar, Ethiopia, 2021: A Structural Equation Modeling Approach - Amare Zewdie; Adane Nigusie; Maereg Wolde; Elyas Melaku Mazengia; Aysheshim Belaineh Haimanot; Adane Habtie; Anteneh Kassa (Hindawi Limited, 2022)
Introduction. Public perceptions of pandemic risk and prevention measures influence adherence to COVID-19 prevention efforts. Even though several factors influence public perceptions, there has been no research on the predictors of COVID-19-related perception in Ethiopia and there are few articles among academic staff worldwide. Thus, this study aims to assess predictors of COVID-19-related perception among Gondar University academic staff. Method. Institutional based cross-sectional study was conducted from April 10 to May 10, 2021. Daniel Soper's calculator was used to determine the sample size. A simple random sampling technique was employed. Data were collected through a self-administered questionnaire and analyzed using Stata V14. Structural equation modeling was performed to identify determinants of COVID-19 related perception. A p value less than 0.05 and a 95% confidence interval of β were used to declare the statistical significance of the variables. Result. A total of 602 academic staff participated. Mean age of participants was 32.38 (±5.83) years. Family size (β = 0.12), chronic illness (β = −0.19), knowledge (β = 0.11), and cues to action (β = 0.43) were significantly associated with perceived susceptibility. Similarly, educational status (β = −0.11), perceived susceptibility (β = 0.61), and cues to action (β = 0.13) were significantly associated with perceived severity. Likewise, knowledge (β = 0.11) and cues to action (β = 0.62) were significant predictors of self-efficacy. Correspondingly, knowledge (β = 0.23), chronic illness (β = 0.09), profession (β = −0.09), perceived susceptibility (β = 0.19), perceived severity (β = 0.23), and self-efficacy (β = 0.29) were significant predictors of perceived benefit. Similarly, age (β = −0.18), profession (β = 0.10), and perceived susceptibility (β = −0.39) were significantly associated with perceived barriers. Conclusion. Several sociodemographic and other factors affect COVID-19 related perceptions. Intervention should consider those factors to improve COVID-19 prevention practice.